Mathematics
yohanaayu79
49

help with number 1 please! it would be very helpful if you would show all the steps so i can learn how to do it. thank you!

+4
(1) Answers
tmosaddegh

The problem to solve is:The goal here is to solve y=-2x-7 and  y=-3x-9 for the variables y and x. First, let's work on your first equation,y=-2x-7This means, see if it can be simplified at all before attempting to solve it. Multiply x and 2Multiply x and 1The x just gets copied along.The answer is xx2*x evaluates to 2xBecause of the minus sign2x becomes - 2xThe answer is -2x-2*x-7 evaluates to -2x-7So, all-in-all, your first equation can be written as: y = -2x-7Now, let's work on your second equation,y=-3x-9 Multiply x and 3Multiply x and 1The x just gets copied along.The answer is xx3*x evaluates to 3xBecause of the minus sign3x becomes - 3xThe answer is -3x-3*x-9 evaluates to -3x-9So, all-in-all, your second equation can be written as: y = -3x-9After this initial survey of the equations, the system of equations we'll set out to solve is: y = -2x-7 and y = -3x-9Let's start by solving y = -2x-7 for the variable y. To isolate the y, we have to divide both sides of the equation by the other variables around the y on the left side of the equation. and this is the final solution to your equation.Next, let's solve y = -3x-9 for the variable x. Move the y to the right hand side by subtracting y from both sides, like this: From the left hand side: y - y = 0The answer is 0From the right hand side: The answer is -3x-9-y Now, the equation reads: 0 = -3x-9-yMove the -3x to the left hand side by adding 3x to both sides, like this: To the left hand side: The answer is 3xTo the right hand side: -3x + 3x = 0xThe answer is -9-y Now, the equation reads: 3x = -9-y  To isolate the x, we have to divide both sides of the equation by the other variables around the x on the left side of the equation. The last step is to divide both sides of the equation by 3 like this: To divide x by 1The x just gets copied along in the numerator.The answer is x3x ÷ 3 = xTo divide -9-y by 3divide each term in -9-y by 3 term by term.-9 ÷ 3 = -3To divide y by 1The y just gets copied along in the numerator.The answer is y-y ÷ 3 =The solution to your equation is: x =Now, plug the earlier result, y=-2x-7, in for y everywhere it occurs in  x=-3-1/3y. This gives x=-3-1/3(-2x-7). Now all we have to do is solve this for x,to have our first solution. Because of the minus sign3 becomes - 3The answer is -31/3 evaluates to Multiply x and 2Multiply x and 1The x just gets copied along.The answer is xx2*x evaluates to 2xBecause of the minus sign2x becomes - 2xThe answer is -2x-2*x-7 evaluates to -2x-7Multiply by -2x-7we multiply by each term in -2x-7 term by term.This is the distributive property of multiplication.Multiply and -2xMultiply 1 and xThe x just gets copied along.x × -2x =Multiply and -71 × -7 =1/3*(-2*x-7) evaluates to -3 - =The answer is-3-1/3*(-2*x-7) evaluates to Move the to the left hand side by subtracting from both sides, like this: From the left hand side: x - =The answer isFrom the right hand side:  - = 0The answer is Now, the equation reads:  =  To isolate the x, we have to divide both sides of the equation by the other variables around the x on the left side of the equation. The last step is to divide both sides of the equation by like this: To divide x by 1The x just gets copied along in the numerator.The answer is x ÷ = x ÷ = -2The solution to your equation is: x = -2Lastly, to find the solution for y, we plug this answer for x into the earlier result that y=-2x-7. This gives y=-2(-2)-7. Now, simplify this. Because of the minus sign2 becomes - 2The answer is -22 becomes - 2Multiply -2 and -21-2*(-2) evaluates to 4-2*(-2)-7 evaluates to -3y= -3So, the solutions to your equations are: y= -3 and x= -2Because of the minus signThe answer is -2

Add answer